BOTANICAL CONTRIBUTIONS TO HUMAN FLOURISHING: A PERSPECTIVE ON THE ROLE OF PLANTS IN ENHANCING HAPPINESS AND FOSTERING VISUAL ART AND SUSTAINABILITY - Datta, Madhushri; Mukherjee, Sobhan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The World Happiness Report 2022 issued by UN Sustainable Development Solutions Network, based on the effects of COVID-19 on the well-being of people worldwide and how they have progressed was released on 18th March 2022. India has been ranked 136 out of 146 countries on the list, far below the neighboring countries like Pakistan (121), Bangladesh (94) and China (72). In this scenario, various methods and parameters to enhance welfare and happiness must be explored and an analysis of the Gross National Happiness should be accomplished. In a society, if everyone works towards a specific workable goal, then the cumulative effect is larger. The Sustainable Development Goals (SDGs) are an example of such an assemblage of 17 intertwined global goals premeditated to be an outline to accomplish an improved and more sustainable future for all people and the world by 2030. To partially fulfill some of the sustainable development goals (https://sdgs.un.org/goals) such as SDG3 Good Health and Well Being, SDG14 Life Below Water, and SDG15 Life on Land, the potentialities of plants need to be fully established and discovered. Botany has long been recognized for its contributions to human well-being, but its role in enhancing happiness, fostering visual art, and promoting sustainability is multifaceted and profound. Many factors influence happiness like genes, circumstances, achievements, marital status, social and professional relationships, and even food. Then, there are some hormones, proper balance of these in the body aids in overall well-being. Plants have the power to uplift and inspire, as evidenced by the burgeoning field of horticultural therapy, which leverages the therapeutic benefits of plant interaction to improve mental health and cognitive function. Moreover, the intricate patterns, vibrant colors, and diverse forms of plants have inspired countless artists, architects, and designers throughout history, influencing the development of visual art and informing sustainable design principles. It is believed that regularly indulging in small pleasures like having a hobby of planting trees, taking a nature walk, protecting plants etc; challenging activities like growing own foods from plants, collecting medicinal plants from the wild, identifying various plants, etc; meeting goals, maintaining close social relationships, and finding purpose beyond oneself - all increases life satisfaction. Sustainable plant cultivation techniques, which are technology-based and environment-friendly, such as urban farming, agroforestry, or easy operative, nature-based, age-old organic farming conducted on any scale, from household to industrial can act as an agent of a sustainable economy. As we navigate the complexities of the Anthropocene, the botanical sciences offer a unique perspective on the interconnectedness of human and environmental flourishing, highlighting the critical role of plants in fostering resilience, creativity, and sustainability